Amazake (Japanese fermented rice beverage) and its potential health benefits - Klaus W. Lange; Yukiko Nakamura (Food Science and Human Wellness)
Amazake is a sweet and non-alcoholic beverage with a long history in Japan. There are two types of amazake, koji amazake produced from rice koji and sakekasu amazake made from sake lees. Amazake has been suggested to be a functional food with various health benefits and cosmetic effects. The efficacy of both koji amazake and sakekasu amazake in improving bowel movements and defecation has been well studied. Amazake may be useful as a food with constipation relieving effects. Furthermore, beneficial effects of amazake on skin barrier function and skin water content in humans have been well established in randomized controlled trials. The findings of amazake effects on gut microbiota, intestinal environment and gut barrier function, mainly demonstrated in animal models, suggest a role of substances contained in amazake as prebiotics. Preliminary evidence indicates the potential value of amazake in the management of obesity, metabolic syndrome and nonalcoholic fatty liver disease. Long-term and excessive intake tests have demonstrated that the consumption of koji amazake is safe. There are few concerns regarding weight gain or increases in blood sugar levels. The functional compounds and mechanisms involved in the health effects of amazake need to be identified in future research.